(untitled) (The Journal of Psychology and Sociology, 2013)
The article is showing the impact of different types of families in the style of coping behavior of teenagers. It was found that the productive and protective coping styles characteristic of teenagers, regardless of family structure. They are mainly determined by the reflection characteristics of the family as teenagers harmonious or problematic. The productive coping styles identified in a harmonious complete and single-parent family. The difference comes only in the fact that teenagers from single-parent families recorded a positive relationship with the absent parent, in connection with its idealization or replacement of its influence support from God. Teenagers from complete families and single-parent problem fixed socially-oriented and defensive coping styles.